Production of probiotic kefir from different plant-based milks - Berra Ceylan; Nilgün Öncül (Cogent Food & Agriculture)
In this study, production of plant-based kefir was carried out using oat, soy and coconut milks. On specific days of the storage (0th, 3rd and 7th day), physicochemical, microbial, and antimicrobial characteristics of the plant-based kefirs were investigated. The pH values of the samples decreased throughout the storage. There was no statistically significant change observed in the ash, dry matter and protein contents of the plant-based kefirs between the storage days (p > 0.05). The carbohydrate values of the plant-based kefirs decreased during the storage, as in the control (p < 0.05). Whey separation in the plant-based kefirs was higher compared to the control. In the plant-based kefirs, the levels of Lactobacillus spp. ranged from 7.88 ± 0.35 to 9.37 ± 0.01 log CFU/mL, Lactococcus spp. ranged from 8.71 ± 0.14 to 9.27 ± 0.15 log CFU/mL, acetic acid bacteria ranged from 8.75 ± 0.16 to 9.49 ± 0.11 log CFU/mL, L. acidophilus ranged from 5.69 ± 0.33 to 6.98 ± 0.35 log CFU/mL, and Bifidobacterium spp. ranged from 5.81 ± 0.34 to 8.57 ± 0.17 log CFU/mL during the storage. Throughout all the storage days, E. coli 0157:H7 showed resistance to the oat and soy kefirs, while S. Typhimurium exhibited resistance to the coconut kefir. This study has provided alternative plant-based fermented beverages for individuals who do not consume or cannot consume animal-derived products.